2007
DOI: 10.1109/tuffc.2007.216
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a parallel resistor on electrical characteristics of a piezoelectric transformer in open-circuit transient state

Abstract: This paper investigates electrical transient characteristics of a Rosen-type piezoelectric transformer (PT), including maximum voltages, time constants, energy losses and average powers, and their improvements immediately after turning OFF. A parallel resistor connected to both input terminals of the PT is needed to improve the transient characteristics. An equivalent circuit for the PT is first given. Then, an open-circuit voltage, involving a direct current (DC) component and an alternating current (AC) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…At present, many efforts have been made to reduce the ring-down time or blind area of ultrasonic transducers, such as full-bridge acoustic emission [ 4 ], parallel resistors [ 12 , 13 ], Golay complementary pairs [ 14 ], amplitude detection [ 15 ], etc. The above methods are usually verified using bulk piezoelectric transducers, not PMUTs with much smaller bandwidth and higher Q .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…At present, many efforts have been made to reduce the ring-down time or blind area of ultrasonic transducers, such as full-bridge acoustic emission [ 4 ], parallel resistors [ 12 , 13 ], Golay complementary pairs [ 14 ], amplitude detection [ 15 ], etc. The above methods are usually verified using bulk piezoelectric transducers, not PMUTs with much smaller bandwidth and higher Q .…”
Section: Introductionmentioning
confidence: 99%
“…When the excitation signal is removed, the full-bridge acoustic emission technique quickly consumes the residual energy. Chang et al [ 12 , 13 ] suggested a parallel resistor to reduce DC time constant and DC response time of the transient response, induced immediately after an AC voltage connected to a bolt-clamped Langevin transducer (BLT). The above methods [ 4 , 12 , 13 ] are effective by increasing the complexity of the peripheral circuit.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence for high power density AC/AC or DC/DC converters, the piezoelectric transformer has become a viable alternative to the magnetic transformer because of higher operating voltages albeit performing a built in bandpass filtering function. Unfortunately, its optimum operating frequency is often hampered by a strong dependence on temperature and voltages applied [20,21].…”
Section: Introductionmentioning
confidence: 99%